Pengaruh Stuktur Modal, Tax Avoidance Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Yani, Mulyani; Stiawan, Hari (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This study aims to examine the Effect of Capital Structure, Tax Avoidance on Firm Value with Dividend Policy as a Moderating Variable. The population in this study are all food and beverage companies listed on the Indonesia Stock Exchange in 2017-2021, a total of 43 companies. Determination of the sample in this study was by purposive sampling technique, so that the number of research samples obtained was 9 companies with 45 observational data. This study uses secondary data types with quantitative research methods. The data analysis technique used in this study is multiple linear regression analysis with a significance level of 5%. Hypothesis testing in this study was carried out using Eviews software version 10. Based on the test results, this study states that 1) Capital structure, Tax Avoidance has an effect on Firm Value. 2) Capital structure has a negative effect on firm value. 3) Tax Avoidance has no effect on Company Value. 4) Dividend Policy is unable to moderate the capital structure on Company Value. 5) Dividend Policy does not moderate Tax avoidance on Company Value.